Methods of creation of intellectual knowledge evaluation system, students in natural language - Kabenov, D.; Murathan, R.; Golenkov, V. (Bulletin of the Karaganda University. Mathematics Series, 2016)
This article provides a framework for the design and development of intelligent information system of knowledge evaluation using an open form tasks, the “open” (without variants of answers) test tasks are considered as efective. Student’s answer entered in a free form gives an opportunity to present student’s views on the subject more accurately. And we evaluate his knowledge, and not based on a guessed answer to the question, which proves the efectiveness of the proposed method. This article presents an approach for text analysis in natural language and organization of query in the knowledge based on the ontology.